2020
DOI: 10.1155/2020/4509576
|View full text |Cite
|
Sign up to set email alerts
|

A Displacement Frequency Response Function‐Based Approach for Locating Damage to Building Structures

Abstract: Frequency response function (FRF) data can provide considerably more information on damage in the desired frequency range as compared to modal data extracted from a very limited range around resonances. Among structural health monitoring techniques, FRF-based methods have the potential to locate structural damage. Conventional structural damage detection technology collects structural response data using contact systems, such as displacement or acceleration transducers. However, installing these contact system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…23 It was concluded that the FRF method more efficiently performs in detecting the damage during the first resonance of the bridge response based on the features including the shift in the resonance and the amplitude changes compared to the performance of the conventional modal parameters such as natural frequencies, modal shapes, and modal damping. The capability of the FRF in damage detection of various structures has been previously obtained in experimental 24 and numerical 25,26 studies. Liu et al 27 revealed that although FRF works only for low-frequency range, the use of FRF shapes caused a more clear damage localization approach in a cantilever beam compared to conventional mode shapes.…”
Section: Review Of Spectral Analysis Approachesmentioning
confidence: 99%
“…23 It was concluded that the FRF method more efficiently performs in detecting the damage during the first resonance of the bridge response based on the features including the shift in the resonance and the amplitude changes compared to the performance of the conventional modal parameters such as natural frequencies, modal shapes, and modal damping. The capability of the FRF in damage detection of various structures has been previously obtained in experimental 24 and numerical 25,26 studies. Liu et al 27 revealed that although FRF works only for low-frequency range, the use of FRF shapes caused a more clear damage localization approach in a cantilever beam compared to conventional mode shapes.…”
Section: Review Of Spectral Analysis Approachesmentioning
confidence: 99%